PENGOBATAN TRADISIONAL ‘‘TOTOMEH’’ DI KELURAHAN KEPENUHAN TENGAH KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - ", Zulkifli; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study analyzes the Totomeh Traditional Medicine in Kepenuhan Tengah Village Kepenuh Subdistrict Rokan Hulu Regency. Totomeh traditional medicine grows and develops in people's lives to meet the treatment needs of diseases believed by the community because of the firmness by the dimension of the Smooth Spirit (Personalistic). A very interesting behavior religious phenomenon that amidst the rapid development of science and technology in the field of modern health, it turns out that in Rokan Hulu Regency as an area known as Negeri Seribu Suluk. The methods of traditional medicine for Totomeh Shaman still exist and can side by side with modern medicine. The theory used refers to the thought of The Law of Three Stages from the founding father of Sociology namely Aguste Comte. Data analysis was carried out with descriptive qualitative data collection techniques in this study were accidental sampling. The research subjects determined is the shamans, the community, religious and health leaders. The results research showed that the traditional method of  treatment medicine using natural ingredients and using Islamic prayers was combined with spells containing the ancient rhyme that is usocialized trough generation. The community used traditional medicine totally because the community was still thick with mystical things and traditional medicines totomeh were up to currently still exsistend use by the people of the Kepenuhan Tengah Village Kepenuhan district Rokan Hulu Regency. Keywords : Traditional Medicine, Totomeh Shaman, Metaphysics